How Do Information Technology Professionals Use Generative Artificial Intelligence? - Santos, Patricia de Oliveira; Figueiredo, Allan Chamon; Moura, Pedro Nuno; Diirr, Bruna; Alvim, Adriana C. F.; Santos, Rodrigo Pereira Dos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: The emergence of generative Artificial Intelligence (AI) and, more recently, the dissemination of Copilot, ChatGPT-3 and similar tools have broadened the discussion about the possibility of using generative AI tools in many professional segments such as health, education, and technological area. Problem: Although some studies explore the potential of generative AI tools to assist Information Technology (IT) professionals in executing specific tasks, they do not delve into the professionals’ characteristics or collect information about multiple generative AI tools usage. Solution: Considering the possibilities brought by generative AI, this study aims to shed light on the perception of IT professionals about generative AI tools and characterize these professionals’ profiles. IS Theory: This research is based on the Technology Acceptance Model. Method: A survey research was carried out with IT professionals so as to identify how these professionals are using generative AI and gather information about these professionals’ profiles. Results: Results show that 70,5% (43 out of 61) of the respondents use some generative AI tool, the majority of whom are software development professionals, and, despite the problems faced when using these tools, 86% of these professionals recommend using them. Contribution: In this study the profile of the IT professionals using generative AI was identified, it was then possible to evaluate the acceptance of such tools among these professionals and identify the main reasons why some of them are not yet using generative AI.